Drivers and barriers of project management practices in logistic industry - Faiqah Masturina, Abd Aziz (2022)
Project Management Practice is a management industry and set of procedures that is extensively used across all Malaysian sectors. However, the importance of project management approaches in the logistics business is becoming increasingly unknown. Numerous additional businesses and countries have followed use adaptation and project management approaches. In reality, the application and adaptation of project management are beginning to be acknowledged, and many sectors are beginning to grasp the significance of project management. This study's purpose was to investigate the recommendations and obstacles for implementing project management approaches in industrial logistics. There are a number of obstacles and guiding principles that lead to the application of project management in industrial logistics. This study will provide four hurdles and four guiding variables in order to examine the usage and significance of project management in the logistics sector. This research is also undertaken to determine the elements that impact the adaption of project management within the logistics business. This study's respondents were persons with at least 10 to 18 years of experience in industrial logistics or a similar industry. This study also used DEMATEL analysis to investigate the link between recommendations and obstacles, as well as the significance of each element. The values examined using DEMATEL will provide a map of the effect connection and variables impacting project management, which will serve as the basis for the proposed model. In addition, the data indicates that knowledge and competence in project management are the most significant element among all others. This study's methodology gives a more in-depth understanding of the elements that must be prioritised and the ones that have the greatest impact on other factors, hence increasing their influence on project management adapters. This model may also be used as a guide to enhance the usage of project management in all Malaysian and international businesses and to improve the performance of project management in a positive direction.